Timing, targets, and transparency: Foreign and domestic resource mobilization to combat COVID-19 - Kennedy, Adam; Resnick, Danielle (International Food Policy Research Institute, 2020)
As the COVID-19 pandemic began spreading globally in March, national governments and the international donor community mobilized quickly to cushion the impact. The speed, uncertainty, and potential severity of the crisis meant that many disbursement approvals occurred faster than usual, and it was difficult to gain a clear picture of where money was going, how different donors were targeting their resources, and how effectively such resources were being utilized. Many governments also began establishing their own funding baskets to respond to COVID-19, often by encouraging donations from politicians, celebrities, businesspeople, and everyday citizens, sometimes without full transparency.